Ecological-Fishery Forecasting of Squid Stock Dynamics under Climate Variability and Change: Review, Challenges, and Recommendations. Issue 4 (2nd October 2021) - Moustahfid, Hassan; Hendrickson, Lisa C.; Arkhipkin, Alexander; Pierce, Graham J.; Gangopadhyay, Avijit; Kidokoro, Hideaki; Markaida, Unai; Nigmatullin, Chingiz; Sauer, Warwick H.; Jereb, Patrizia; Pecl, Gretta; de la Chesnais, Thibaut; et al.
Abstract: Globally, cephalopods support large industrial-scale fisheries and small-scale to partly large-scale local artisanal fisheries. They are of increasing economic importance as evidenced by the rapid rise in their global landings from 1950 to 2014. Cephalopods are sensitive to environmental variability and climate change and many if not all species show wide fluctuations in abundance. This is most evident in ommastrephid nerito-oceanic squid since their life cycle is associated with boundary currents that are changing with climate change. The inter-annual variability in catch presents challenges for fishers and managers due to the 'boom-or-bust' nature of the fishery. A key barrier to rational management of squid fisheries is the low level of development of fishery forecasting. Despite substantial progress made in relating squid population dynamics to environmental variability and change, several challenges remain to develop forecast products to support squid fisheries management. Ideally, squid fisheries management needs a forecasting system that includes all time-scales of forecasting, and especially short - and medium-terms forecasts. The present overview first provides current knowledge of the effects of climate change and variability on squid population dynamics, challenges and opportunities to advance ecological-fishery forecast products, and finally a roadmap is proposed for future development of forecasts products to support squid sustainable fisheries management. As for the adoption of specific forecasting methods to the squid fishery management process, what is important is the relationship between needs, feasibility, and the ultimate success of a forecast will be determined by whether it is used by end-users.